1984
DOI: 10.1139/v84-073
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence from the reactions of ozone with sulphur compounds

Abstract: . Can. J. Chem. 62, 417 (1984). Emissions from excited SO2 in its singlet state ('B, and/or 'A,) and triplet state ('B,) have been observed in gas-phase chemiluminescent reactions of ozone with a number of sulphur compounds. The compounds studied are carbon disulphide, thiophene, diallyl sulphide, diallyl disulphide, dimethyl sulphide, dimethyl disulphide, and thiophenol. The reaction pathways responsible for the formation of excited molecules are discussed. The remarkable similarity between the emission sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These compounds are subsequently mixed with the substrate that remained outside of the irradiated volume and some of them may react within the time of residence or during sampling for analysis. During ozonolysis, a brown colored oil deposited in the annular reactor 60 which could be dissolved in acetonitrile for GC/MS-analysis. It contained, in addition to the oxidation products already mentioned, 2,2′-methylenedithiophene (25), 3-(2-thienyl)-2propenal (26) and diethylsulfone (27, compounds drawn in red in Schemes 5 and 6).…”
Section: Intermediate Products Of the Reaction Pathways To The Minera...mentioning
confidence: 99%
“…These compounds are subsequently mixed with the substrate that remained outside of the irradiated volume and some of them may react within the time of residence or during sampling for analysis. During ozonolysis, a brown colored oil deposited in the annular reactor 60 which could be dissolved in acetonitrile for GC/MS-analysis. It contained, in addition to the oxidation products already mentioned, 2,2′-methylenedithiophene (25), 3-(2-thienyl)-2propenal (26) and diethylsulfone (27, compounds drawn in red in Schemes 5 and 6).…”
Section: Intermediate Products Of the Reaction Pathways To The Minera...mentioning
confidence: 99%
“…Akimoto et al [lO] reported that the emitting species from the reactions of 03 with H2S, CH3SH, and CH3SCH 3 is SO 2. Becker et al [Ill briefly examined the chemiluminescence from the reactions of 03 with CH3SCH 3 and (CH3S) 2, Arora and Chatha [12] observed emission from electronically excited SO 2 produced in the gas-phase reaction of 03 with thiophene, diallyl sulfide, diallyl disulfide, CH3SCH 3, (CH3S) 2, and thiophenol. Glinski et al [13,14] have observed emission from the reaction of 03 with CH3SH ,andGlinski and Dixon [15] observed emission from the reactions of 03 with (CH3S) 2 and (CH3)2S0.…”
Section: Reactions With 03mentioning
confidence: 99%
“…An alternative strategy for measuring DMS is using gas phase chemiluminescence (CL) based on the chain reaction of DMS with ozone to form the sulfur monoxide radical (SO⋅), which then reacts with ozone to produce light with a wavelength maximum (λ max ) at 370 nm [25,26]. The reaction is summarized in eq.…”
Section: Introductionmentioning
confidence: 99%